Antennal ultrastructure of Leptidea Billberg, 1820 (Pieridae: Dismorphiinae: Leptideini) and its taxonomic implications - Llorente-Bousquets, Jorge; Castro-Gerardino, Diana Jimena (Zootaxa, 2018)
We present the results of the first examination and comparative analysis of the ultrastructure of the antennae in seven species of Leptidea Billberg, 1820 (Pieridae). The results add further support to the hypothesis that the subfamily Dismorphiinae is composed of the tribes Leptideini and Dismorphiini. We summarize the results in a table and discuss the ultrastructure similarities and differences between the two tribes. Following a previously proposed framework, we trace the progression of character states and discuss the significance of the results in the context of varying phylogenetic hypotheses for Leptidea, with special emphasis on biogeography. We include a brief description of the terms we employ to described the main characters and types of sensilla of the antennal club of Leptidea. Remarkable antennal sexual dimorphism is noted in L. gigantea.